Individual device active cooling for enhanced system-level power density and more uniform temperature distribution - Zeng, Y.; Hussein, A.; Castellazzi, A. (2018)
This paper provides a method of individual device active cooling system to balance the temperature distribution of system-level power density. 3L-ANPC GaN inverter was used to test and prove the feasibility of it in using multi-level systems.